Call-Fleming Syndrome (Reversible Cerebral Artery Vasoconstriction) and Aneurysm Associated with Multiple Recreational Drug Use - Doniel Drazin; Michael J. Alexander (Case Reports in Neurological Medicine, 2013)
Drug abuse represents a significant health issue. Evidence suggests that recreational drug use has a direct effect on the cerebral vasculature and is of greater concern in those with undiagnosed aneurysms or vascular malformations. The authors report a case of thunderclap headache with a negative head CT and equivocal lumbar puncture after a drug-fueled weekend. The patient underwent diagnostic cerebral angiogram which demonstrated multisegmental, distal areas of focal narrowing of the middle, anterior, posterior, and posterior inferior cerebral artery and an incidental aneurysm. It is often difficult to determine the exact origin of symptoms; thus we were left with a bit of a chicken or the egg debate, trying to decipher which part came first. Either the aneurysm ruptured with associated concomitant vasospasm or it is a case of Call-Fleming syndrome (reversible cerebral artery vasoconstriction) with an incidental aneurysm. The authors proposed their management and rationale of this complex case.